Health disparities and advertising content of women's magazines: a cross-sectional study - Victorio Maria; Vargas Reynaldo; Amador Xavier; Lopez Janina; Patton Annie; Tom Laura; Mikail Amy; Duerksen Susan C; Kustin Brenda; Sadler Georgia (BMC, 2005)
Abstract Background Disparities in health status among ethnic groups favor the Caucasian population in the United States on almost all major indicators. Disparities in exposure to health-related mass media messages may be among the environmental factors contributing to the racial and ethnic imbalance in health outcomes. This study evaluated whether variations exist in health-related advertisements and health promotion cues among lay magazines catering to Hispanic, African American and Caucasian women. Methods Relative and absolute assessments of all health-related advertising in 12 women's magazines over a three-month period were compared. The four highest circulating, general interest magazines oriented to Black women and to Hispanic women were compared to the four highest-circulating magazines aimed at a mainstream, predominantly White readership. Data were collected and analyzed in 2002 and 2003. Results Compared to readers of mainstream magazines, readers of African American and Hispanic magazines were exposed to proportionally fewer health-promoting advertisements and more health-diminishing advertisements. Photographs of African American role models were more often used to advertise products with negative health impact than positive health impact, while the reverse was true of Caucasian role models in the mainstream magazines. Conclusion To the extent that individual levels of health education and awareness can be influenced by advertising, variations in the quantity and content of health-related information among magazines read by different ethnic groups may contribute to racial disparities in health behaviors and health status.